An architecture for synchronising cloud file storage and organisation repositories. Issue 5 (3rd September 2019) - Andriani, Gil; Godoy, Eduardo; Koslovski, Guilherme; Obelheiro, Rafael; Pillon, Mauricio
ABSTRACT: Cloud computing providers have disseminated dynamic storage provisioning delivered to end users as on-demand services. Although cloud file storage and sharing has become popular among home users, the access requirements, performance expectations and usage characteristics are different for organisations, and were not originally considered by popular applications and tools for synchronising files between cloud providers and local repositories. Moreover, multisite organisations traditionally have legacy file storage and wide-area networking solutions to support their business systems. Typically, the file repositories are replicated between sites using private communication links. The combination of legacy storage solutions interconnected through private links with cloud-based file storage is a challenging task. In this context, this paper introduces Cloud4NetOrg, a client architecture for cloud file storage and multisite repository synchronisation. We implemented prototypes of this architecture that interact with two popular cloud file services (DropBox and OneDrive), and the experimental results indicate a promising application in collaborative environments with several LANs. Indeed, Cloud4NetOrg decreases the synchronisation time and the total data transferred from/to cloud repositories by using the organisation repositories as a hierarchical cache system. Cloud4NetOrg is proposed for geographically distributed organisations composed of dynamic and temporary collaborative groups. The interaction between employees is based on file sharing. Commonly, sites are interconnected by a private network and have an internal data storage repository. A single site can have multiple subnetworks to interconnect the collaborative groups. In addition, home-office users collaborate through the Internet, usually using size-limited storage devices. GRAPHICAL ABSTRACT: